The Effect of The Practical-Based Learning Model Toward Science Process Skills and Concept Comprehension of Regulation System - Sari, Prima Mutia; Sudargo, Fransisca; Priyandoko, Didik (Jurnal Pendidikan Indonesia, 2017)
The aim of this research was to analyze the influence of practical-based learning model on the concept of regulation system of the science process skills and concept comprehension of student. Research method was a quasi-experimental with the matching pretest-posttest design. The research population consisted of all students in class XI in one of senior high schoolÂ  in West Sumatra with a total population of 150 students. Sampling technique was a cluster random sampling. Sample consisted of 26 students of class experiment through practical-based learning and 26 students of class control through verificationÂ  practical learning. The instrument consist of a science process skills test and concept comprehension test. The data was analyzed using the Mann-Whitney test, Normalized gain. The results showed that there was a significant difference in science process skills and concept comprehension between the experimental and the control class. Herewith, it has been concluded that the practical-based learning model on the concept system of regulation improvement the science process skills and concept comprehension.